Impact of a nurse‐led limited risk factor modification program on arrhythmia outcomes in patients with atrial fibrillation undergoing catheter ablation. (15th January 2020) - Yaeger, Amaryah; Keenan, Brendan T.; Cash, Nancy R.; Parham, Tara; Deo, Rajat; Frankel, David S.; Schaller, Robert D.; Santangeli, Pasquale; Nazarian, Saman; Supple, Gregory E.; Arkles, Jeffrey; Kumareswaran, Ramanan; et al.
Abstract: Background: We have previously demonstrated the feasibility of a nurse‐led risk factor modification (RFM) program for improving weight loss and obstructive sleep apnea (OSA) care among patients with atrial fibrillation (AF). Objective: We now report its impact on arrhythmia outcomes in a subgroup of patients undergoing catheter ablation. Methods: Participating patients with obesity and/or need for OSA management (high risk per Berlin Questionnaire or untreated OSA) underwent in‐person consultation and monthly telephone calls with the nurse for up to 1 year. Arrhythmias were assessed by office ECGs and ≥2 wearable monitors. Outcomes, defined as Arrhythmia control (0‐6 self‐terminating recurrences, with ≤1 cardioversion for nonparoxysmal AF) and Freedom from arrhythmias (no recurrences on or off antiarrhythmic drugs), were compared at 1 year between patients undergoing catheter ablation who enrolled and declined RFM. Results: Between 1 November 2016 and 1 April 2018, 195 patients enrolled and 196 declined RFM (body mass index, 35.1 ± 6.7 vs 34.3 ± 6.3 kg/m 2 ; 50% vs 50% paroxysmal AF; P = NS). At 1 year, enrolled patients demonstrated significant weight loss (4.7% ± 5.3% vs 0.3% ± 4.4% in declined patients; P < .0001) and improved OSA care (78% [n = 43] of patients diagnosed with OSA began treatment). However, outcomes were similar between enrolled and declined patients undergoing ablation (arrhythmia control in 80% [n = 48] vs 79% [n = 38]; freedom from arrhythmia in 58% [n = 35] vs 71% [n = 34]; P = NS). Conclusion: Despite improving weight loss and OSA care, our nurse‐led RFM program did not impact 1‐year arrhythmia outcomes in patients with AF undergoing catheter ablation.